2012
DOI: 10.1111/1471-0528.12072
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative post‐conisation human papillomavirus testing for early detection of treatment failure in patients with cervical intraepithelial neoplasia: a pilot study

Abstract: Objective To evaluate the feasibility and utility of intraoperative post-conisation human papillomavirus (IOP-HPV) testing and cytology to detect treatment failure in patients with cervical intraepithelial neoplasia grades 2-3 (CIN2-3).Design Prospective observational pilot study.Setting Barcelona, Spain.Population A cohort of 132 women treated for CIN2-3 by loop electrosurgical conisation.Methods An endocervical sample was obtained intraoperatively with a cytobrush from the cervix remaining after the conisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
3
24
0
1
Order By: Relevance
“…Safe return of women who have undergone conization to the primary screening program requires a high negative predictive value, which we obtained with both cytology (99.2%) and HPV testing (99.8%). Similar values have been found in previous studies, with, however, a tendency to slightly higher estimates for the negative predictive value of HPV than that of cytology . As the prevalence of relapse after conization is low, differences in negative predictive value should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 87%
“…Safe return of women who have undergone conization to the primary screening program requires a high negative predictive value, which we obtained with both cytology (99.2%) and HPV testing (99.8%). Similar values have been found in previous studies, with, however, a tendency to slightly higher estimates for the negative predictive value of HPV than that of cytology . As the prevalence of relapse after conization is low, differences in negative predictive value should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 87%
“…This is one of the few studies available evaluating intraoperative HPV testing as an early marker for disease recurrence in cervical HSIL . It also highlights the value of HPV 16 genotyping in the assessment of this risk.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study by Torné et al . suggested that an HPV test performed intraoperatively could be an early marker of HSIL recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 97 studies, published between Jan 1, 1975, and Feb 1, 2016, were eligible for inclusion in the meta-analysis (figure 1), 65 of which were included in the previous meta-analysis by Ghaem-Maghami and colleagues, 14 assessing the risk of treatment failure associated with incomplete excision. Additionally, 15 studies [96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] were identified from previous meta-analyses 9,111,112 assessing the accuracy of post-treatment HPV and or cytology testing to detect residual or recurrent CIN2+ and contained data for the margin status. 16 new reports 15,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] were added that had not been included in previous reviews.…”
Section: Resultsmentioning
confidence: 99%